Thyroid Abscess: Challenges in Diagnosis and Management. (23rd May 2018) - Yedla, Niharika; Pirela, Daniela; Manzano, Alex; Tuda, Claudio; Lo Presti, Saberio
Thyroid abscess is an uncommon infectious pathology. The thyroid is highly resistant to infection due to high iodine content, capsular encasement, and rich vascularity. Acute suppurative thyroiditis represents <1% of thyroid diseases that could potentially become a life-threatening endocrine emergency. A 48-year-old woman with AIDS presented with 3 days of fever, tender neck swelling, and methicillin-resistant Staphylococcus aureus bacteremia. Apart from leukocytosis, initial laboratory values including thyroid function tests were normal. The initial plain computed tomography scan of the neck and ultrasound scan of the neck were inconclusive as well. By day 4, she worsened, and on repeat computed tomography scan of the neck with contrast, multiloculated abscesses in the thyroid and retro pharynx were seen, which needed emergent drainage. Acute suppurative thyroiditis, a rare disease, occurs in patients with either preexisting disorders of the thyroid or in the immunocompromised. The most common pathogen is Staphylococcus aureus . In our case, we highlight the fact that initial imaging may be negative in the early stages of acute suppurative thyroiditis and lead to an erroneous diagnosis of subacute thyroiditis. There are less than 5 cases of methicillin-resistant Staphylococcus aureus suppurative thyroiditis reported.